2016
DOI: 10.1111/ijpo.12101
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation of miRNA coding sequences putatively associated with childhood obesity

Abstract: The current work identified three CpG sites located in coding regions of three miRNAs (miR-1203, miR-412 and miR-216A) that were differentially methylated between obese and non-obese children, suggesting a role of miRNA epigenetic regulation in childhood obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 29 publications
(34 reference statements)
2
35
0
1
Order By: Relevance
“…A total of 500 ng of purified DNA was treated with sodium‐bisulfite using the EZ‐96 DNA Methylation Kit (Zymo Research Corporation, Irvine, CA, USA) according to the manufacturer's protocol. Modified DNA samples were whole‐genome amplified and hybridized to Infinium Human Methylation 450K BeadChips (Illumina, San Diego, CA, USA) as detailed elsewhere (Mansego, Garcia‐Lacarte, Milagro, Marti, & Martinez, 2017). The scanning of the samples was carried out with the Illumina HiScanSQ system, and the image intensities were extracted with the GenomeStudio Methylation Software Module, v1.9 (Illumina).…”
Section: Methodsmentioning
confidence: 99%
“…A total of 500 ng of purified DNA was treated with sodium‐bisulfite using the EZ‐96 DNA Methylation Kit (Zymo Research Corporation, Irvine, CA, USA) according to the manufacturer's protocol. Modified DNA samples were whole‐genome amplified and hybridized to Infinium Human Methylation 450K BeadChips (Illumina, San Diego, CA, USA) as detailed elsewhere (Mansego, Garcia‐Lacarte, Milagro, Marti, & Martinez, 2017). The scanning of the samples was carried out with the Illumina HiScanSQ system, and the image intensities were extracted with the GenomeStudio Methylation Software Module, v1.9 (Illumina).…”
Section: Methodsmentioning
confidence: 99%
“…The EZ DNA Methylation Kit (Zymo Research, Irvine, CA, U.S.A.) was used for the bisulfite conversion of 1000 ng of genomic DNA. Infinium methylation assay was carried out with the Illumina Infinium Human Methylation 450 Bead Chip (Illumina, San Diego, CA, U.S.A.) by Making Genetics (Making Genetics, Noáin, Spain) . Data analysis was performed using the ChAMP pipeline, resulting in a dataset of 433 237 CpG sites with good hybridization quality.…”
Section: (A) Summary Of the Ewas Association Analysis Performed And Tmentioning
confidence: 99%
“…Infinium methylation assay was carried out with the Illumina Infinium Human Methylation 450 Bead Chip (Illumina, San Diego, CA, U.S.A.) 5 by Making Genetics (Making Genetics, No ain, Spain). 5 using the ChAMP pipeline, 6 resulting in a dataset of 433 237 CpG sites with good hybridization quality. To reduce possible bias due to cell heterogeneity, DNA methylation data were corrected with the algorithm described by Houseman et al 7 and adjusted for the covariates sex and age.…”
mentioning
confidence: 99%
“…Li et al (26) have also reported that that miR-216a-5p is involved in diabetes and targeted genes including ANGPTL4, ANXA9, CFH, CHI3L2 and INPP4B (26). Mansego et al (27) found that miR-216a-5p might be involved in miRNA mediated epigenetic regulation in childhood obesity and the coding regions of miR-216a-5p were methylated (27). Furthermore, it was suggested that miR-216a-5p had an impact on chronic kidney diseases (28), nephrotic syndrome (29) and end-stage failing hearts (30).…”
Section: Discussionmentioning
confidence: 99%